2005
DOI: 10.1002/mus.20450
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary predictors of survival in amyotrophic lateral sclerosis: Use in clinical trial design

Abstract: The rapidity of progression of amyotrophic lateral sclerosis (ALS) to death or respiratory failure impacts patients, clinicians, and clinical investigators. This study compared the abilities of various pulmonary function tests to predict tracheostomy-free survival. We evaluated 95 ALS patients by determining upright and supine forced vital capacity (FVC), maximal inspiratory (MIP) and expiratory (MEP) pressures, arterial partial pressure of carbon dioxide (PaCO 2 ), and transdiaphragmatic sniff pressures (Pdi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 20 publications
5
58
1
2
Order By: Relevance
“…FVC essentially measures the full extent of a breath capable by a patient, excluding the dead space of the lung and upper airways. Other measures of pulmonary function in ALS have also been studied, including maximal voluntary inspiratory or expiratory pressures, but it is not clear that these offer any advantage over the FVC [39].…”
Section: Respiratory Functionmentioning
confidence: 99%
“…FVC essentially measures the full extent of a breath capable by a patient, excluding the dead space of the lung and upper airways. Other measures of pulmonary function in ALS have also been studied, including maximal voluntary inspiratory or expiratory pressures, but it is not clear that these offer any advantage over the FVC [39].…”
Section: Respiratory Functionmentioning
confidence: 99%
“…Such studies have utilized a variety of methods, including measures of maximal isometric strength, activities of daily living scales, and a number of functional measures, most commonly pulmonary function. [1][2][3]17,21,33 Although they have shown considerable success in documenting and predicting the course of disease, 15,18,25,27,30,36 their ability to represent the underlying pathophysiology of ALS is limited as these measures of impairment or disability do not directly measure the changes occurring within the motor unit (MU) pool as a result of the disease.…”
mentioning
confidence: 99%
“…If NIV can reduce diaphragmatic muscle overload and reduce macro-motor unit drop-out, then it may have a favorable effect on the course of the disease. In several studies NIV has been proposed to decrease the rate of decline of lung function, 4,6,12 but another study showed that, while the rate of lung function decline slows over time, this slowing was independent of initiation of NIV. 5 There may still be advantages to earlier NIV initiation that are unrelated to a modification of the progress of the disease.…”
Section: See the Original Studies On Pages 1424 And 1433mentioning
confidence: 99%